Hyperacute ischemic stroke without lesions on diffusion‐weighted imaging in a patient treated with rtPA thrombolysis. Issue 3 (16th March 2014) - Jing, Zhen; Zhang, Shijun; Tang, Jingjing; Xu, Anding; Ruan, Yiwen; Huang, Li'an
Key Clinical Message We report a comatose patient with severe neurological deficits who was without spontaneous language or movement. He had a good response to recombinant tissue plasminogen activator (rtPA) thrombolysis even though there were no detectable lesions on diffusion‐weighted imaging (DWI). DWI is very sensitive for diagnosing hyperacute ischemic stroke, and rtPA thrombolysis is the best treatment. However, rtPA thrombolysis in ischemic stroke patients without lesions on DWI has rarely been reported.